Philosophy by Other Means The Arts in Philosophy and Philosophy in the Arts. - Pippin, Robert B. (University of Chicago Press, 2021)
"The relationship between philosophy and aesthetic criticism has occupied Robert Pippin throughout his illustrious career. Whether discussing film, literature, or modern and contemporary art, Pippin's claim is that we cannot understand aesthetic objects unless we reckon with the fact that some distinct philosophical issue is integral to their meaning. In his latest offering, Philosophy by Other Means, we are treated to a collection of essays that builds on this larger project, offering profound ruminations on philosophical issues in aesthetics along with revelatory readings of Henry James, Marcel Proust, and J. M. Coetzee"--